2010
DOI: 10.1186/1479-5876-8-75
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of allogeneic umbilical cord blood mononuclear cell therapy for degenerative conditions

Abstract: BackgroundThe current paradigm for cord blood transplantation is that HLA matching and immune suppression are strictly required to prevent graft versus host disease (GVHD). Immunological arguments and historical examples have been made that the use of cord blood for non-hematopoietic activities such as growth factor production, stimulation of angiogenesis, and immune modulation may not require matching or immune suppression.Methods114 patients suffering from non-hematopoietic degenerative conditions were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 19 publications
1
56
0
1
Order By: Relevance
“…These studies are best addressed in a larger animal model. There is one report in which 114 patients suffering from with 13 varied neurologic injuries or diseases all received allogeneic UCB MSC transplants with no preconditioning, HLA matching or immune suppression (Yang et al 2010). All hematologic and immunologic parameters and serum chemistries were in the normal range for these patients.…”
Section: Discussionmentioning
confidence: 97%
“…These studies are best addressed in a larger animal model. There is one report in which 114 patients suffering from with 13 varied neurologic injuries or diseases all received allogeneic UCB MSC transplants with no preconditioning, HLA matching or immune suppression (Yang et al 2010). All hematologic and immunologic parameters and serum chemistries were in the normal range for these patients.…”
Section: Discussionmentioning
confidence: 97%
“…The feasibility of allogeneic UCB cell infusions into patients with non-hematopoietic degenerative conditions was evaluated in the study conducted by Yang et al [38]. One hundred fourteen patients with paraplegia, ataxia, multiple or amyotrophic lateral sclerosis, among other conditions, received multiple (up to 4e5) intrathecal injections combined with intravenous infusion of allogeneic HLA-unmatched UCB mononuclear cells (1e3 Â 10 7 cells per treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Although HUCB cells are less immunogenic, long term studies should be considered to evaluate the long term safety with or without immunosuppression. Jozwiak et al and Yang et al have reported on using HUCB cells for the safe treatment of a single case of global brain ischemia and in a number of neurological disorders (including stroke) respectively with short term follow-up (Jozwiak et al, 2010;Yang et al, 2010). Second, because HUCB collection can only be performed at single timepoints (i.e.…”
Section: Discussionmentioning
confidence: 99%